Pendampingan Pembelajaran Praktek Tayamum dan Wudhu di TPQ Al-Khasanah Desa Barong Sawahan - Kholis Firmansyah; Rina Dian Rahmawati; Ema Siti Nur Azizah (Jumat Keagamaan: Jurnal Pengabdian Masyarakat, 2022)
In the world of education, it is very necessary to teach religion, especially education in the Al-Qur'an education park (TPQ) AL-Khasanah, Barongsawahan village, this TPQ proves how important it is that religious education is taught to children to build their character, problems in learning the practice of tayamum and this ablution is the need to repeat the problem of ablution and tayamum practice. So from this problem, the owner of the Al-Qur'an Education Park (TPQ) AL-Khasanah needs to repeat the learning of the practice of tayamum and ablution. This lesson aims to teach TPQ AL-Khasanah children to better understand how to perform ablution and tayammum properly and correctly. The results of the practice of tayamum and ablution show that the teacher's role in fostering the character of students at TPQ AL-Khasanah, Barongsawahan village, Ibu Masamah is as the owner of the TPQ who becomes a role model for TPQ AL-Khasanah students, teachers who master the material, patient mentors and creative coaches or skilled, and the role can be carried out well. Through this role, the character values ​​of children who are humble, disciplined, religious, creative or skilled, independent and responsible in carrying out their duties can be developed. Through learning the practice of tayamum and ablution, they can increase the knowledge of TPQ in AL-Khasanah Barongsawahan children. village, jombang district.